Finders keepers a novel - King, Stephen (Scribner, 2020)
Wake up, genius." So announces deranged fan Morris Bellamy to iconic author John Rothstein, who once created the famous character Jimmy Gold and hasn't released anything since. Morris is livid, not just because his favorite writer has stopped publishing, but because Jimmy Gold ended up as a sellout. Morris kills his idol and empties his safe of cash, but the real haul is a collection of notebooks containing John Rothstein's unpublished work...including at least one more Jimmy Gold novel. Morris hides everything away-the money and the manuscripts no one but Gold ever saw-before being locked up for another horrific crime. But upon Morris's release thirty-five years later, he's about to discover that teenager Pete Saubers has already found the stolen treasure-and no one but former police detective Bill Hodges, along with his trusted associates Holly Gibney and Jerome Robinson, stands in the way of his vengeance... Not since Misery has Stephen King played with the notion of a reader and murderous obsession, filled with "nail biting suspense that's the hallmark of [his] best work.